Research Assessment – Navigating Pitfalls and Promoting Change - Flores Bueso, Yensi; Dole, Hervé; Whitaker, Kirstie; Winther, Jan-Gunnar; Larssen, Tanja (Septentrio Conference Series, 2023)
Watch VIDEO. The main theme of the Munin conference is scholarly communication in its myriad of forms. The push for a reform of research assessment argues for precisely the need to recognize and reward a wider set of research activities and competencies. The demand – and initiative – for change will surely impact how and where research is disseminated and communicated. A key question then is how to evaluate research activities and outputs beyond academic publications. With this panel we welcome a discussion on research assessment that brings together perspectives from all the topics of this year’s Munin conference. We invite you to add your insights and diverse expertise to this panel that will reflect on questions such as: how do we measure the impact of citizen science, or document quality in innovative research practices and scholarly outputs? And how to ensure consensus on assessment methods for a wider and more inclusive range of research activities within a diverse academic landscape?